2020
DOI: 10.7326/m20-1515
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Impact of Angiotensin-Converting Enzyme Inhibitors or Angiotensin-Receptor Blockers on SARS-CoV-2 Infection in Adults

Abstract: Background: The role of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin-receptor blockers (ARBs) in COVID-19 disease susceptibility, severity, and treatment is unclear.Purpose: To evaluate, on an ongoing basis, whether use of ACEIs or ARBs either increases risk for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or is associated with worse COVID-19 disease outcomes, and to assess the efficacy of these medications for COVID-19 treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
146
3
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 42 publications
6
146
3
3
Order By: Relevance
“…Interestingly, mortality was slightly reduced (11%) in ACEIs/ARBs users of SARS-CoV-2 positive patients compared to those not using these medications although it was statistically insigni cant. These ndings are consistent in line with other analyses carried out by independent researchers 10,11 . Most importantly, the ndings of current analysis support different professional societies recommendations for continuing ACEIs/ARBs irrespective whether it is contraindicated for other clinical conditions not just COVID-19 reason 1 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, mortality was slightly reduced (11%) in ACEIs/ARBs users of SARS-CoV-2 positive patients compared to those not using these medications although it was statistically insigni cant. These ndings are consistent in line with other analyses carried out by independent researchers 10,11 . Most importantly, the ndings of current analysis support different professional societies recommendations for continuing ACEIs/ARBs irrespective whether it is contraindicated for other clinical conditions not just COVID-19 reason 1 .…”
Section: Discussionsupporting
confidence: 93%
“…Another systematic review conducted by Mackey K et al 2020 reported the association of ACEIs/ARBs users versus non-ACEIs/ARBs users with SARS-CoV-2 test positivity in limited perspectives 11 . However, severity of COVID-19 illness was not reported for the patients with or without ACEIs/ARBs users but was adjusted with other covariates in this analysis, which certainly renders lacking robust evidence regarding these con icts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We complemented an amended [8] meta-analysis and a living systematic review [9,10] with an updated search through 7/4/2020 in the PubMed, Cochrane, and medRxiv.org databases. A PRISMA owchart is shown in Figure S1 in the supplementary section.…”
Section: Methodsmentioning
confidence: 99%
“…The foremost hypotheses describing the pathway through which SARS-CoV-2 enters the cells is related to the involvement of angiotensin-converting enzyme-2 (ACE2). Although this enzyme has been described as the receptor for coronaviruses [ 4 ], upregulation of ACE2 due to ACE inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) has not been consistently demonstrated in human and animal studies (reported in [ 5 ]). ACE2 serves a counterbalancing role in the renin–angiotensin–aldosterone system (RAAS), i.e., it cleaves away (i) phenylalanine from angiotensin (Ang) II, converting it to Ang-(1-7), and (ii) leucine from Ang I, converting it to Ang-(1-9).…”
Section: Introductionmentioning
confidence: 99%